Prokrastinasi dalam Pelaksanaan Small Group Discussion Mahasiswa Tingkat II Program Studi Sarjana Keperawatan STIKes Dharma Husada - Erawan, Annisa Nur; Airin, Zalfa Novita; Rejeki, Yunita Fitri (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2025)
Introduction and Methods Small Group Discussion (SGD) is a student-centered learning method that emphasizes collaborative group work. The implementation of SGD in various higher education institutions shows varying levels of preference for different SGD models, as well as diverse levels of procrastination. Therefore, evaluation of SGD implementation is necessary to ensure its alignment with students’ needs and the applied curriculum. This study aimed to identify procrastination in the implementation of Small Group Discussion (SGD) among second-year undergraduate nursing students at STIKes Dharma Husada. This research employed a descriptive quantitative method with a total sample of 60 respondents, selected using a total sampling technique. The instrument used was a procrastination questionnaire for the implementation of SGD at STIKes Dharma Husada, adapted from Ferrari. Results Based on the frequency distribution, the study revealed that procrastination among second-year undergraduate nursing students at STIKes Dharma Husada (99.3%) was predominantly at a moderate level. Across four sub-variables of procrastination, the findings were as follows: Perceived Time was at a low level (65.2%), Intention–Action was at a moderate level (64.9%), Emotional Distress was at a moderate level (100%), and Perceived Ability was at a moderate level (57.9%). Conclusion and Recommendations Procrastination was observed across four stages. The most influential aspect affecting SGD was emotional distress (100%), while the least influential aspects were perceived time, intention–action, and perceived ability. Based on these findings, it is recommended that students enhance their time management skills and make sustained efforts to achieve better academic performance.